Diversity and distribution of the Italian Aesculapian snake Zamenis lineatus: A phylogeographic assessment with implications for conservation. (31st March 2017) - Salvi, Daniele; Lucente, Daniela; Mendes, Joana; Liuzzi, Cristiano; Harris, D. James; Bologna, Marco A.
Abstract: Geographic range size and genetic diversity are key correlates of extinction risk and evolutionary potential of a species, with species occupying smaller geographic ranges and showing limited genetic diversity assumed to be more threatened by environmental changes. The Italian Aesculapian snake Zamenis lineatus is a narrow‐range endemic of southern Italy and Sicily, once considered as part of the widespread species Z. longissimus . To date, we still lack comprehensive data on geographic range and intraspecific diversity of Z. lineatus . In this study, we analysed 106 Aesculapian snakes across the Italian Peninsula and Sicily in order to define the genetic diversity and distribution range of Z. lineatus, its possible range overlap with Z. longissimus and to assess whether hybridization occurs at the species' range boundaries. We combined genetic data from mitochondrial and nuclear DNA markers with phenotypic data suitable for taxonomic identification. The observed phylogeographic pattern of Z. lineatus suggests: (i) a reduced peninsular range size, about a half of what is currently considered; (ii) limited genetic diversity and weak population structure; (iii) the occurrence of pervasive introgressive hybridization with Z. longissimus in the eastern contact zone. Together, results from this study indicate a higher extinction risk for Z. lineatus than previously appreciated and provide directions for future studies on the hybridization at the contact zone(s) between Z. lineatus and Z. longissimus . Abstract : We analysed genetic and phenotypic data from Aesculapian snakes across the Italian Peninsula and Sicily in order to assess the genetic diversity and distribution range of Z. lineatus, its range overlap with Z. longissimus and whether hybridization occurs at the species' range boundaries. The phylogeographic pattern of Z. lineatus suggests: (i) a reduced peninsular range size; (ii) limited genetic diversity and weak population structure; and (iii) the occurrence of pervasive introgressive hybridization with Z. longissimus in the eastern contact zone.